SHANK1 deletions in males with autism spectrum disorder - Sato, Daisuke; Endris, Volker; Röth, Ralph; Rappold, Gudrun (The American journal of human genetics, 2012)
Recent studies have highlighted the involvement of rare (<1% frequency) copy-number variations and point mutations in the genetic etiology of autism spectrum disorder (ASD); these variants particularly affect genes involved in the neuronal synaptic complex. The SHANK gene family consists of three members (SHANK1, SHANK2, and SHANK3), which encode scaffolding proteins required for the proper formation and function of neuronal synapses. Although SHANK2 and SHANK3 mutations have been implicated in ASD and intellectual disability, the involvement of SHANK1 is unknown. Here, we assess microarray data from 1,158 Canadian and 456 European individuals with ASD to discover microdeletions at the SHANK1 locus on chromosome 19. We identify a hemizygous SHANK1 deletion that segregates in a four-generation family in which male carriers—but not female carriers—have ASD with higher functioning. A de novo SHANK1 deletion was also detected in an unrelated male individual with ASD with higher functioning, and no equivalent SHANK1 mutations were found in >15,000 controls (p = 0.009). The discovery of apparent reduced penetrance of ASD in females bearing inherited autosomal SHANK1 deletions provides a possible contributory model for the male gender bias in autism. The data are also informative for clinical-genetics interpretations of both inherited and sporadic forms of ASD involving SHANK1.